Neuromuscular adaptations to 2,5-week high-intensity interval training with compression garments in female ice hockey players - Piirainen, J. M.; Kinnunen, J. V.; Piitulainen, H. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
INTRODUCTION: High-intensity interval training (HIIT) is commonly used training method to improve performance. HIIT increases power and speed performance (Naimo et al. 2015), possibly because of improved motor control. Utilization of the compression garments (CG) during the exercise may enhance performance and recovery (Hamlin et al. 2012), and thus may enhance the training response. We studied neuromuscular adaptations to HIIT and possible benefits of the CG for training response. METHODS: Fourteen female ice-hockey players were divided into compression garment (CG, height 165 ± 6 cm, weight 68 ± 12 kg, age 22 ± 4 years, N = 6) and noncompression garment (no-CG; height 166 ± 5 cm, weight 66 ± 13 kg, age 22 ± 3 years, N = 8) training groups. Both groups performed 2.5 weeks HIIT by running in 9.5 degree uphill. Rate of force development (RFD) was measured from plantar flexors. Levels of voluntary motor drive (V-wave/maximal M-wave) and spinal alpha-motoneuron excitability (H-reflex/20% M-wave) were quantified during maximal voluntary contraction from soleus muscle before and after the training. Light cells where used to measure acceleration and maximal speed during on-ice performance. RESULTS: Both groups improved RFD (CG 15.6 ± 12.3%, p < 0.05; no-CG 14.9 ± 18.9%, p < 0.05) during the training. In addition, V-wave responses increased by 20.3 ± 14.7% in CG group (p < 0.05), while in no-CG group increment was only 13.4 ± 15.9%. No significant changes were observed in H-reflex amplitude (CG 0.0 ± 48.6%; no-CG 4.5 ± 36.5%), nor in on-ice skating performance. DISCUSSION: A significant HIIT-training-induced increase in V-wave amplitude implied increased or better-synchronized neural motor drive through the spinal alpha-motoneurons during maximal isometric contraction (Aagaard et al. 2002). However, utilization of CG didn`t cause additional improvement in the force production, even though the level of voluntary motor drive was enhanced. It can be suggested that, possible benefits of CG should be confirmed with studies utilizing longer training periods and including more muscle groups such as quadriceps muscles.